Challenges of Pakistani Community in Bahrain: The Role of Pakistan Embassy - Rafiq, Saad Bin (Journal of Pakistan Administration, 2022)
Workers’ migration from Pakistan has remained a significant contributor to the national economy by way of providing employment and financial support through remittances. The bulk of this migration has taken place (and continues to do so) to the Gulf Cooperation Council (GCC) countries. The Kingdom of Bahrain remains the fifth largest destination for Pakistani workers.2 However, these workers face a number of challenges in Bahrain that are the outcome of several factors.
Keywords: Role of Pakistan Embassy; employment; financial support; Gulf Cooperation Council